Nation-Building Predicament, Transition Fatigue, and Fear of State Collapse: An Emerging Phenomenon in Post-2015 Ethiopia - Gebrewahd, Meressa Tsehaye (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Ethiopia, evolved from Tigray, is known by its history of having been an empire (e.g., the Axumite kingdom) and having been independent. The fundamental weakness of the Ethiopian state has been the lack of inclusive national consensus, hampered by national oppression and the dilemma of democratizing a feudal state. The post-1991 TPLF-EPRDF-led Ethiopia has been experimenting with federalist nation-building to address Ethiopia’s historical contradictions: national and class oppression. The 1995 FDRE Constitution established a federal system and subsequently recognized the right of nations to self-determination including secession, self-administration, and local development. The constitution also declared that the Ethiopian nations were the “sovereign owners” of the constitution. However, the coming of Abiy Ahmed to power and his policy reforms based on ‘neo-pan-Ethiopianism’ opened the box of Pandora of secessionist, irredentist, and federalist forces opposing his plan to recentralize the ethnic federation, as it happened similarly in the case of former Yugoslavia. PM Abiy’s reforms have been branded as those of the ‘Mikael Gorbachev of Ethiopia’ for his sweeping campaign against the 27 years of federalist control. The article investigates the nation-building aspirations, transition fatigue, the predicaments of secessionist, federalist, and assimilationist narratives, and the subsequent fear of ‘state collapse’ in the post-2018 crisis in Ethiopia.